Enhanced thermal coarsening resistance in a nanostructured aluminum-cerium alloy produced by additive manufacturing. (1st November 2021) - Henderson, Hunter B.; Hammons, Joshua A.; Baker, Alexander A.; McCall, Scott K.; Li, Tian T.; Perron, Aurélien; Sims, Zachary C.; Ott, Ryan T.; Meng, Fanqiang; Thompson, Michael J.; Weiss, David; Rios, Orlando
Graphical abstract: Highlights: Rapid solidification inherent to selective laser melting additive manufacturing induces a nanoscale dispersion of insoluble intermetallic particles in bulk Al-Ce alloys. Particle interconnectivity can be controlled based on solidification conditions, influencing material flow behavior and load sharing. The particle dispersion is extremely resistant to coarsening and property degradation after thermal exposure due to low solubility and diffusion, with behavior resembling a metal matrix nanocomposite. Insoluble eutectic alloy systems Al-Ce offer a promising pathway for alloys designed to take advantage of the specific formation conditions inherent to metal additive manufacturing. Abstract: Decreasing microstructural length scales to the nanoscale is a proven way of increasing strength, but the intrinsic metastability of such structures typically makes them susceptible to thermally activated coarsening. Recent advances in additive manufacturing permit bulk-nanostructured materials to be produced through rapid solidification, but like other metastable materials the as-built structures typically coarsen rapidly with even modest thermal exposure. Here, selective laser melting is employed to produce an Al-Ce-based alloy with high mechanical strength arising from the as-built microstructure, which can be controlled by build conditions. In addition, the alloy exhibits extreme resistance to thermal coarsening up to 400 °C and superior strength retention compared to conventional Al alloys after extended thermal exposure. The near-zero solubility of Ce in Al and potent solid solution strengthening of Mg enable this behavior without requiring heat treatment. This result demonstrates that combining insoluble alloying elements with additive manufacturing is a viable method of producing exceptionally stable bulk nanoscale alloys.